Pemanfaatan Ruang Terbuka Studio Pengembang Media Pembelajaran Sebagai Pusat Inkubasi Batik Berbasis Triplehelix Collaboration Bernilai Income Generating - Annisa Ayu Salsabila; Eka Putri Surya; Mohamad Firzon Ainur Roziqin; Abdul Rahman Prasetyo; Adinda Marcelliantika; Alby Aruna; Ginanjar Atma Wijaya (MES Bogor, 2024)
The use of the open space of the learning media developer studio as a batik incubation center based on the Triple Helix Collaboration with income generating value aims to increase innovation and productivity in the batik industry through collaboration between academics, industry, and the government. This program utilizes the open space of the studio to create an ecosystem that supports the development of skills, creativity, and entrepreneurship in batik production. Various methods are used, including in-depth technical training, creative workshops to encourage innovation, and facilitation of market access to expand the range of batik products. The results of the program show a significant improvement in the technical skills and entrepreneurial capacity of the participants, which contributes to their economic growth and competitiveness. The implementation of the program focuses not only on improving individual skills, but also on strengthening networks and relationships between academia, industry, and government to create synergistic and sustainable collaborations. Through this approach, the economic value and competitiveness of the local batik industry can be significantly improved, providing a long-term positive impact on the community and the local economy.